Evaluación agronómica de tres variedades de arveja de amarre a tres diferentes pisos altitudinales - Cisneros Chicaiza, Yessenia Elizabeth (2023)
The province of Carchi is considered one of the most important agricultural provinces in the north of the country, where the main source of income for its inhabitants is focused on dairy farming and potato cultivation. El Carchi presents several microclimates which favor the production of a variety of crops, one of these is the cultivation of mooring peas, considered the second in importance after potato cultivation, especially in the northern part of the province. The pea crop is very versatile, which maintains its productivity in various areas of the Carchi province, even where the climate is warm, however, there are no studies that support the efficiency and adaptation of this crop, therefore, the present The objective of the research was to evaluate 3 varieties of mooring peas San Isidro, Andina and Churosa, having as study variables: agronomic behavior through 4 stages within the BBCH scale and yield (t.ha-1 ), at different altitudinal floors, being these El Colorado 2840 m a.s.l.\; Cuesaca 2663 m.a.s.l. and Cunquer 2272 m a.s.l. The results obtained show that in all altitudinal floors the varieties were adapted, however, it was in Cunquer where there was a better production of this crop with 16.91 t.ha-1 , followed by Cuesaca with a production of 11.92 t.ha-1 and El Colorado with 1.88 t.ha-1 . Likewise, the phenological study where the emergence, beginning of the elongation of the stem, full flowering and fruit formation was evaluated, the best results were obtained in Cunquer, which stands out for presenting a warm environment with an average temperature of 20.54 ° C, which is directly related to yield, both in pod and grain.